Factors compromising the auditor independence: a study on the perception of Malaysian publicly listed companies / Norziana Lokman and Nur'Atiqah Mohd Bakri - Lokman, Norziana; Mohd Bakri, Nur'Atiqah (Universiti Teknologi MARA, 2020)
One of the critical responsibilities of the auditor is to form an independent view of the company's financial performance in the auditor's statement. In Malaysia, the issue of auditor independence has recently become prominent due to the 1MDB scandal. Hence, this study focuses on determining the factors that compromise auditor independence in Malaysian publicly listed companies. This study has identified four main factors which are perceived to affect auditor independence. They are audit fees, audit tenure, auditor market competition and non-audit services. This study aims to investigate the relationship between the four compromised factors and auditor independence. A set of questionnaires was developed and distributed among 280 accountants, financial managers and chief financial officer of Malaysian publicly listed companies. Each respondent is required to assess the compromised factors that contribute to auditor independence using a 'Five-point Likert scale'. The data collected then were tested and analysed using correlation and regression analysis. Findings reveal that audit tenure has positively and significantly influenced the auditor independence. Moreover, other factors have no significant influence on auditor independence. This study contributes to the literature of auditor independence and provides further evidence that long audit tenure can enhance the independence of auditors from the perspective of listed companies. Thus, the professional bodies, regulators and policymakers should carefully consider the recommendation on the restriction of auditor rotation and audit firm rotation before making it mandatory.